Influence of temperature and nickel catalyst on the structural and optical properties of indium oxide nanostructured films synthesized by chemical vapor deposition technique. (September 2021) - Aper, T.M.; Yam, F.K.; Beh, K.P.
Abstract: This work reports the synthesis of indium oxide pyramids, octahedrons, and faceted nanostructures on silicon and nickel-coated silicon substrates via carbothermal reduction of In2 O3 powder assisted by a 1% hydrogen/balance nitrogen mixed gas as forming and carrier gas. The influence of deposition temperature on the morphology, structural, and optical properties of the produced films was investigated by varying the source temperature from 850 to 1000 °C. Characterization of the In2 O3 nanostructures was performed using FESEM, EDX, XRD, and UV–vis spectrophotometry. Material growth, film thickness, crystallites size, and crystallinity were observed to be enhanced with increased deposition temperature. The use of Ni as a catalyst resulted in the production of high yield films even at the low growth temperature. XRD revealed polycrystalline films with preferential growth in the (222) plane. Films synthesized on Si substrate showed more regular reflection as compared to those grown on Ni/Si. The optical band gap was found to decrease from 3.4 to 2.89 eV with increased deposition temperature. Bandgap narrowing was attributed to the increase in grain size and film thickness.